Brugeraspekter ved emneklassifikationer til fagsproglige ressourcer - Weilgaard Christensen, Lise Lotte (LexicoNordica, 2018)
This article focuses on terminological resources and user aspects when creating subject classifications for in-house term bases in private enterprises. After an introduction to subject classifications in term bases, the article presents user aspects from the classifications developed during the DANTERM project. Furthermore, the article presents the results from a small survey among private enterprises conducted for this article. Finally, a proposal is offered for best practice for creating subject classifications for the term bases in questions. The results are compared to the usage of labels in LGP (language for general purposes) dictionaries.